2009
DOI: 10.1128/jb.00175-09
|View full text |Cite
|
Sign up to set email alerts
|

Gemfibrozil Inhibits Legionella pneumophila and Mycobacterium tuberculosis Enoyl Coenzyme A Reductases and Blocks Intracellular Growth of These Bacteria in Macrophages

Abstract: We report here that gemfibrozil (GFZ) inhibits axenic and intracellular growth of Legionella pneumophila and of 27 strains of wild-type and multidrug-resistant Mycobacterium tuberculosis in bacteriological medium and in human and mouse macrophages, respectively. At a concentration of 0.4 mM, GFZ completely inhibited L. pneumophila fatty acid synthesis, while at 0.12 mM it promoted cytoplasmic accumulation of polyhydroxybutyrate. To assess the mechanism(s) of these effects, we cloned an L. pneumophila FabI enoy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
0
14
1
Order By: Relevance
“…We found that GEM was effective against Mabc infection in vivo using mouse model. A prior study reported the antimycobacterial activity of GEM in bacteriological medium and in macrophages [54]. Importantly, we found that GEM did not exert a direct antimycobacterial effect against Mabc.…”
Section: Discussioncontrasting
confidence: 42%
“…We found that GEM was effective against Mabc infection in vivo using mouse model. A prior study reported the antimycobacterial activity of GEM in bacteriological medium and in macrophages [54]. Importantly, we found that GEM did not exert a direct antimycobacterial effect against Mabc.…”
Section: Discussioncontrasting
confidence: 42%
“…We are not aware of any study reporting the transcriptomic response of microorganisms to low doses of the lipid regulator gemfibrozil. Recently, however, it was shown that high doses of GM inhibited bacterial fatty acid synthesis (28). A variety of responses, including an increase in acetylcholinesterase, succinate dehydrogenase, and glucose-6-P dehydrogenase activities, has also been observed for fish cells at low GM doses (41).…”
Section: Discussionmentioning
confidence: 99%
“…Garbe et al reported some toxicity of fibrates on M. tuberculosis (24). Gemfibrozil has been indeed shown to inhibit M. tuberculosis growth with a potential action on a mycobacterial enoyl coenzyme A (24,25). More recently, Kim et al reported that fibrates could lower the bacterial burden and inflammation in an M. smegmatis macrophage invasion model by a PPAR␣-independent pathway (26).…”
mentioning
confidence: 99%